Optische in‐situ Prozessverfolgung und ‐steuerung. (December 2013) - Gäbler, Johannes; Stenzel, Olaf; Wilbrandt, Steffen; Kaiser, Norbert
<x xml:space="preserve">Abstract</x> In situ optical monitoring and process control: Measuring transmittance and reflectance of optical coatings during deposition Optical monitoring techniques havebecome indispensable parts of deterministic preparation strategies for sophisticated optical coatings. Traditional versions of optical broadband monitoring are based on measurements of the transmission spectrum or alternatively the reflection spectrum of the growing film. In the case of practically loss‐free samples, both approaches principally deliver equivalent information. In the case of absorbing coatings, the information gained from the different spectra may be no more equivalent. Instead, it may be reasonable to record both spectra simultaneously, in order to get a more complete picture of the status of the growing film. We present a corresponding measurement setup designed for use in typical coating evaporation processes and demonstrate its application to the deposition of alumina coatings as well as aluminum mirrors.